Insight into the synergism between MnO2 and acid sites over Mn–SiO2@TiO2 nano-cups for low-temperature selective catalytic reduction of NO with NH3. Issue 4 (9th January 2018) - Zheng, Siyi; Song, Lei; Tang, Siyang; Liu, Changjun; Yue, Hairong; Liang, Bin
Abstract : A novel Mn–SiO2 @TiO2 nano-cup catalyst with synergy of MnO2 and acid sites for efficient low-temperature SCR reaction. Abstract : The rational synthesis of low-temperature catalysts with high catalytic activity and stability is highly desirable for the selective catalytic reduction of NO with NH3 . Here we synthesized a Mn–SiO2 /TiO2 nano-cup catalyst via the coating of the mesoporous TiO2 layers on SiO2 spheres and subsequent inlay of MnO2 nanoparticles in the narrow annulus. This catalyst exhibited superior catalytic SCR activities and stability for low-temperature selective catalytic reduction of NO with NH3, with NO conversion of ∼100%, N2 selectivity above 90% at a temperature ∼140 °C. The characterization results, such as BET, XRD, H2 -TPR, O2 /NH3 -TPD and XPS, indicated that this nano-cup structure catalyst possesses high concentration and dispersion of Mn 4+ active species, strong chemisorbed O − or O2 2− species and highly stable MnO X active components over the annular structures of the TiO2 shell and SiO2 sphere, and thus enhanced the low-temperature SCR performance.